Stabilizer Kamera 2-Axis Dengan Pid Control Berdasarkan Setpoint pada Atmega 328 - Adryan Chiko Pratama; Dahnial Syauqy; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Advances in technological developments currently affect human life, one of which is camera technology. Currently the camera has a technology that serves to reduce vibration when shooting called Image Stabilization, but this technology produces less precise images therefore required stabilizer. It is expected that with this research can help the problem of tilted in shooting from smartphone camera. In this research used a sensor gyroscope and accelerometer located on one unit of MPU-6050 which can be read value using Arduino Nano microcontroller. The sensor value include in the calculation of PID Control which variables Kp, Ki and Kd are searched using trial and error method. Based on the test that has been done, the research have the conclusion that the accuracy level of MPU-6050 sensor value to the average arc of system error difference 0,4 ° and percentage of system error is 0,25%. The difference or the resulting error value due to measurement accuracy using a protractor is below 1 °. In testing the accuracy of the servo angle to the setpoint obtained the average percentage error of both servo angles reached 0.17% with a large error of degree 0.24 °. Then on testing the stabilizer response speed to achieve stable (settling time) found the average speed reached the stable system that is 0.92 seconds.